Current advance in bioconversion of methanol to chemicals - Wenming Zhang; Meng Song; Qiao Yang; Zhongxue Dai; Shangjie Zhang; Fengxue Xin; Weiliang Dong; Jiangfeng Ma; Min Jiang (Biotechnology for Biofuels, 2018)
Abstract Methanol has become an attractive substrate for biotechnological applications due to its abundance and low-price. Chemicals production from methanol could alleviate the environmental concerns, costs, and foreign dependency associated with the use of petroleum feedstock. Recently, a growing fraction of research has focused on metabolites production using methanol as sole carbon and energy source or as co-substrate with carbohydrates by native or synthetic methylotrophs. In this review, we summarized the recent significant progress in native and synthetic methylotrophs and their application for methanol bioconversion into various products. Moreover, strategies for improvement of methanol metabolism and new perspectives on the generation of desired products from methanol were also discussed, which will benefit for the development of a methanol-based economy.